Anticancer activity of palladium-based complexes against triple-negative breast cancer - Vojtek, Martin; Marques, Maria P.M.; Ferreira, Isabel M.P.L.V.O.; Mota-Filipe, Hélder; Diniz, Carmen (Drug discovery today, 2019)
•TNBC is an unmet medical need with poor survival rates and no targeted therapy.•TNBC resists conventional chemotherapy and surgical strategies.•A review of 121 Pd(II) complexes studied in TNBC cell lines is presented.•Pd(II) complexes show promising cancer selectivity and activity against TNBC. Treatment of triple-negative breast carcinoma (TNBC) remains an unmet medical need with no targeted therapy available to date. Accounting for 10–30% of all human breast cancer tumors, this mammary carcinoma subtype has a particularly poor prognosis owing to its high metastatic potential, aggressive biology and limited pharmacological treatment options. Platinum chemotherapeutics are the mainstay therapy in patients with TNBC but their clinical use is limited by severe toxicity and acquired resistance. Palladium-based complexes are appealing alternative metal-based drugs because of significant similarities regarding structure and coordination chemistry with the platinum agents. This review summarizes the knowledge gathered so far on 121 Pd(II) complexes, emphasizing their anticancer activity and putative pharmacological targets toward TNBC.